P05.32 Update on a metronomic antiangiogenic combination therapy for recurrent atypical teratoid rhabdoid tumor. (19th September 2018) - Slavc, I; Peyrl, A; Chocholous, M; Czech, T; Dieckmann, K; Haberler, C
Abstract: Background: Prognosis of patients with recurrent atypical teratoid rhabdoid tumor (ATRT) is dismal despite intensive therapy including high-dose chemotherapy with stem cell rescue. An evolving alternative approach to conventional chemotherapy is to target neovascularisation by interfering with tumor angiogenesis at various levels. We report on 12 patients with recurrent ATRT treated with an antiangiogenic combination therapy. Patients and Methods: From 03/2008 to 02/2018, 12 patients were diagnosed with recurrent ATRT (6 first, 6 multiple recurrences), three had germ line mutations. Treatment consisted of an antiangiogenic multidrug-regime including IV bevacizumab, oral thalidomide, celecoxib, fenofibrate, and etoposide alternating with cyclophosphamide, and augmented with intraventricular therapy (etoposide and liposomal cytarabine) with or without focal radiotherapy. Median age at start of antiangiogenic therapy was 3 (1–12) years. Results: As of 05/2018, 6/12 patients are alive and in CR for 123, 90, 45, 9, 6 and 3 months after start of antiangiogenic therapy, the first three off therapy. One patient died of another cause 50 months after her recurrence in CR and without evidence of tumor at autopsy. OS for the whole cohort was 47.7 ± 16.6% at 3 years and 31.8 ± 17.1% at 5-years with a median OS of 22.8 months (KI 0.0–66.8). Therapy was generally well tolerated and toxicities were manageable. Conclusion: The proposed antiangiogenic regimen is currently being evaluated for medulloblastomas in an international phase II protocol (MEMMAT; ClinicalTrials.gov Identifier: NCT01356290). The same approach seems to be also efficacious in recurrent ATRTs and warrants further evaluation.